Amelioration of diabetic nephropathy in db/db mice treated with tibetan medicine formula Siwei Jianghuang Decoction Powder extract. Issue 1 (December 2018) - Lai, Xianrong; Tong, Dong; Ai, Xiaopeng; Wu, Jiasi; Luo, Yu; Zuo, Fang; Wei, Zhicheng; Li, Yanqiao; Huang, Wanyi; Wang, Wenqian; Jiang, Qing; Meng, Xianli; et al.
Abstract Siwei Jianghuang Decoction Powder (SWJH) documented originally inthe Four Medical Tantras-Blue Glaze exhibited beneficial effects on diabetic nephropathy (DN) via combined synergistically action of multiple formula components including Curcumae longae Rhizoma, Berberidis dictyophyllae Cortex, Phyllanthi Fructus and Tribuli Fructus. This study investigated the effects of SWJH on DN in db/db mice and possible underlying mechanisms. The ten weeks old db/db mice treated with SWJH by intra-gastric administration once a day for 8 weeks. After 8 weeks, body weight, water and food intake of mice were recorded. The level of fasting blood glucose (FBG) was measured. Serum creatinine (Scr), blood urea nitrogen (BUN), urine microalbumin (UMAlb), serum uric acid (UA) and urinary albumin excretion (UAE) were detected. An enzyme-linked immunosorbent assay was performed to test serum vascular endothelial growth factor (VEGF) and transforming growth factor-β1 (TGF-β1). Real-time PCR and Western blot analysis were used to test mRNA and protein expression of hypoxia inducible factor-1α (HIF-1α), VEGF and TGF-β1 in kidney tissue. SWJH treatment significantly reduced the levels of FBG, Scr, BUN, UMAlb, UA and UAE and retarded renal fibrosis. SWJH treatment further significantly reduced serum TGF-β1 level and downregulated the expression of HIF-1α, VEGF and TGF-β1 at both mRNA and protein levels. Principal component analysis and partial least squares regression and hierarchical cluster analysis demonstrated that SWJH treatment significantly ameliorated renal damage in DN mice. These consequences suggested that SWJH formulations were effective in the treatment of DN through regulating the HIF-1α, VEGF and TGF-β1 overexpression.